Identification of FDA-approved Drugs Targeting Breast Cancer Stem Cells Along With Biomarkers of Sensitivity - Bhat-Nakshatri, Poornima (Nature Publishing Group, 2013)
Recently developed genomics-based tools are allowing repositioning of Food and Drug Administration (FDA)-approved drugs as cancer treatments, which were employed to identify drugs that target cancer stem cells (CSCs) of breast cancer. Gene expression datasets of CSCs from six studies were subjected to connectivity map to identify drugs that may ameliorate gene expression patterns unique to CSCs. All-trans retinoic acid (ATRA) was negatively connected with gene expression in CSCs. ATRA reduced mammosphere-forming ability of a subset of breast cancer cells, which correlated with induction of apoptosis, reduced expression of SOX2 but elevated expression of its antagonist CDX2. SOX2/CDX2 ratio had prognostic relevance in CSC-enriched breast cancers. K-ras mutant breast cancer cell line enriched for CSCs was resistant to ATRA, which was reversed by MAP kinase inhibitors. Thus, ATRA alone or in combination can be tested for efficacy using SOX2, CDX2, and K-ras mutation/MAPK activation status as biomarkers of response.